Problem-Based Science Learning Strategy in Improving Critical Thinking Skills of Elementary School Students: Literature Review - Qothrunnada, Qothrunnada; Zainuri, Baiq Nabila Saufika; Gunawan, Gunawan (Indonesian Journal of Elementary and Childhood Education, 2025)
The limited critical thinking skills of elementary school students in science education pose a significant challenge in 21st-century education. This Systematic Literature Review (SLR) aims to identify the most effective Problem-Based Learning (PBL) strategies for enhancing these skills. An analysis was conducted on 20 articles (2016–2025) sourced from Scopus, Web of Science, and Google Scholar databases. Synthesis results indicate that both pure PBL and its integration with STEM, Augmented Reality (AR), and digital media consistently improve students' analytical, interpretive, and evaluative abilities. Key findings emphasize that PBL's effectiveness depends heavily on authentic problem presentation and structured scaffolding. Digital technology integration is proven to strengthen scientific reasoning by visualizing abstract concepts. This study concludes that PBL becomes more transformative through multimodal approaches. Consequently, teachers must enhance their TPACK competence to design problem scenarios relevant to elementary students' characteristics to create more impactful science learning.